ANALISIS PENGEMBANGAN PELATIHAN TARUNA AAL KORPS PELAUT GUNA MENDUKUNG PENUGASAN TNI AL - Yahya Junarko; Yanu Madawanto; O.B. Dirgantara; H. Lestianto (Universitas Muhammadiyah Tapanuli Selatan, 2022)
The Marine Defense Management Study Program is carried out by the Marine Department (Deppel) which is in charge of organizing the education process for Operation Corps AAL Cadets to become Indonesian Navy officers who have a fighting spirit, professionalism, discipline, pride, hard work and smart work and have high abilities. The Marine Defense Management Study Program also forms cadets who are able to master and develop and apply the science of marine defense management in assignments or service as well as community service. This research on the analysis of the development of the AAL cadet training for the Operation corps to support the assignment on the Navy warships is expected to provide theoretical benefits, namely applying the Strength, Weakness, Opportunity, and Threats (SWOT) methods to determine development strategies and the Interpretative Structural Modeling (ISM) method. ) to prioritize strategies in training development. After calculating and processing research data, it is found that at level I produces a sub-strategy (WO4), namely Focusing on AAL cadets of the Operation Corps with their work and responsibilities for developing training and personnel in a better direction, one of which is by thinking that they can carry out their duties and responsibilities. good service as a junior officer. From these results, it is hoped that AAL will be able to produce graduates who are in accordance with the demands of assignments on the Navy warships.